2000
DOI: 10.1034/j.1600-0420.2000.078006687.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced posterior vitreous detachment by intravitreal sulfur hexafluoride (SF6) injection in patients with nonproliferative diabetic retinopathy

Abstract: ABSTRACT.Purpose: To induce posterior vitreous detachment (PVD) in patients with nonproliferative diabetic retinopathy (NPDR) by injecting an intravitreal gas bubble of SF6 and to compare the evolution of the diabetic retinopathy between eyes with gas induced PVD and non-injected eyes without PVD. Methods: An intravitreal gas bubble of SF6 was injected via the pars plana in twelve eyes of twelve patients with NPDR and no previous PVD. Subsequent clinical, ultrasonographic and angiographic controls were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 4 publications
(4 reference statements)
1
9
0
2
Order By: Relevance
“…Previous studies 3,13 have suggested that induction of PVD concurrent with vitrectomy and removal of traction on the macula can lead to improvement in macular edema. For these reasons, ophthalmologists have been exploring methods other than surgery for induction of PVD, and pharmacologic vitreolysis represents a major and important goal of vitreoretinal surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies 3,13 have suggested that induction of PVD concurrent with vitrectomy and removal of traction on the macula can lead to improvement in macular edema. For these reasons, ophthalmologists have been exploring methods other than surgery for induction of PVD, and pharmacologic vitreolysis represents a major and important goal of vitreoretinal surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent with vitrectomy, intravitreal injection of varying materials, including hyaluronidase, tissue plasminogen activator (TPA), plasmin, and sulfur hexafluoride, has been used to induce PVD. 13,14 The purpose of this study was to evaluate the role of intravitreal injection of TPA for the treatment of DME refractory to standard treatment in patients with nonproliferative diabetic retinopathy.…”
mentioning
confidence: 99%
“…All treated eyes developed a PVD. 20,21 Efficacy of pneumatic VMT release, as reported in studies so far, seems higher than that of ocriplasmin. 2,4,11,19 The observed weak and nonsignificant effect of ocriplasmin on pseudophakic eyes (13.4% in the ocriplasmin group vs 3.8% in the placebo group) 11 makes the traction release in all three of our pseudophakic cases all the more interesting.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these studies, intravitreal gas injection may offer a minimally invasive, easily accessible, and low-cost alternative treatment for patients with VMT. 2,[16][17][18][19][20][21] In addition, the safety profile of intravitreal gas injection has been well established in pneumatic retinopexy in retinal detachments 22,23 and pneumatic displacement of submacular hemorrhages. 24,25 We report a case series of 20 eyes in 17 patients that were treated with an intravitreal gas injection to release VMT.…”
Section: Introductionmentioning
confidence: 99%
“…Neben der chirurgischen Lösung der VMT und der eventuellen Entfernung von epiretinalen Membranen mittels Vitrektomie besteht seit 2012 die Möglichkeit der enzymatischen Vitreolyse [16][17][18][19]. Obwohl schon vor Jahren die Induktion einer Glaskörperabhebung durch intravitreale Gasapplikation gezeigt wurde, hat diese Methode erst in den letzten Jahren bei der VMT ein vielversprechendes Indikationsgebiet gefunden [20][21][22].…”
Section: Vitreomakuläre Traktion -Behandlungsmethodeunclassified